TEACHERS' CLINIC. - Yankee, Glen G.; Moss, Kermit C.; Cobby, E. Kennedy; Lynn, Edward S.; Homburger, Richard H.; Dunn, Clarence L.; MacDougall, Colville (The Accounting Review, 1960)
Abstract The path leading to a degree with a major in accounting is a rugged one at best. Obstacles are to be encountered at every turn. Many an eager student has dashed confidently down this path only abruptly to encounter a sizeable obstacle known as partnership dissolution resulting from the admission of a new partner. Managerial Accounting as a course of study represents a recent addition to the accounting curriculum of many schools of higher education. The addition of this course reflects the current demand for an approach to accounting that emphasizes the utilization of accounting data for management planning and control. At the present time many accounting departments are in the process of reevaluating their entire accounting curriculum to determine to what extent present offerings may continue to serve their traditional purpose as well as fulfill the need for an approach which takes into greater consideration the managerial aspect. The non-accounting major terminates his study of accounting with the Managerial Accounting course. The accounting major, almost without exception, takes the same Managerial Accounting course as the non-major which means that he takes the course between Introductory Accounting and Intermediate Accounting.